Caracterização geomorfológica, morfotectônica e morfométrica da Folha Itapororoca 1:25.000, Paraíba, Brasil - Souza, Alexandre dos Santos (2016)
This study aimed to analyze the interrelation ships between geology, relief and hydrography of the area of Itapororoca sheet (SB.25-YAV-4-NO), at scale 1:25,000, with equidistance between the contour lines of 10m, in the state of Paraiba, demonstrating how there lief of the are a shows clear influence of structural control on the configuration of relief and drainage network. From this perspective, it is emphasized that the know ledge of geomorphological features is an in dispensable way for the elaboration of plans geared to various purposes, such as: engineering works, environmental issues, agricultural development, mineral exploration, among others. The integrated analysis of morphostructural peculiarities present in relief and river drainage systems, allowed to infer about the role of tectonic deformations that occur through structural efforts, revealing numerous morphostructural features in the sedimentary covers and the grounds of the Precambrian crystalline basement. The research was conspicuous by analyzing the qualitative and quantitative aspects of geomorphology and drainage network, with the aid of cartographic products and the application of morphometric indices. The development of cartographic material, essential for qualitative analysis, consisted in the confection of hypsometric, slope and geomorphology thematic maps, Digital Elevation Model (DEM) and topographic profiles. The quantitative evaluation and neotectonics consisted of application of morphometric parameters of Slope/Length (SL), Valley Floor Width/Valley Height (VF) Ratio and Asymmetrical Factor (AF).The thematic maps and MDE were generated by specific software, based on data extracted from Itapororoca sheet 1:25,000 by manual vectorization, which allowed unprecedented detail of the geomorphological and hydrographic pattern present in the area. The results exposed several anomalies in the study area, for example, altimetric discrepancies present in the area of geological unit Itapororoca Felsic Volcanic Rock (northwestern) and Trays (northeast portion), indicating that the region was affected by faulting and compressive efforts that defined several anomalies, such as: anomalous rectilinear drainage patterns, lattice and associated subtypes; abrupt channels inflections forming orthogonal angles; isolated and compressed meanders; and morphostructural faulting with guidance compatible with regional tectonic structures in northeastern Brazil. Substantiating the evidence, the values obtained with the application of morphometric parameters showed that neotectonic events affected the drainage network of the study area. Thus, it is concluded that the combined analysis of the studied elements made blunt results about neotectonics performance that configures morphotectonic environments and drainage anomalies in the area of Itapororoca sheet 1:25,000.